PENGARUH APLIKASI PUPUK KOMPOS TERHADAP TOLERANSI SELADA(LACTUCA SATIVA) PADA SUHU 360C-400C - Noriani; Yonathan Suryo Pambudi (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2025)
This study analyzes the growth tolerance of lettuce (Lactuca sativa) to high temperatures with the application of compost fertilizer at Jl. Klodran Selatan No. 30, Kronggahan RT 02/RW 07, Banturan, Colomadu, Karanganyar, Central Java. Lettuce growth is inhibited at temperatures (36°C-400C) at this research location. The objectives are to evaluate the effect of high temperature on lettuce growth, the impact of heat stress, and the effectiveness of compost fertilizer in improving tolerance to high temperatures and yield quality. A completely randomized design (CRD) with five treatments (compost percentage: 0%, 30%, 50%, 60%, 100%) and four replications was used. Observed parameters included plant height and leaf color. Results showed that the 50% compost and 50% soil treatment yielded the tallest plants, but plant condition deteriorated by week 5. Excessive compost use (60% and 100%) reduced growth. Further analysis is needed to explain the interaction between high temperature, compost concentration, and lettuce growth. Lettuce cultivation in tropical regions is hampered by high temperatures causing heat stress and reduced yields. This research investigates the effect of organic compost application on lettuce tolerance to temperatures (36°C-400C) at Jl. Klodran Selatan No. 30, Karanganyar. To evaluate the effect of high temperature on lettuce growth. To identify the impact of heat stress on lettuce due to high temperatures. To analyze how compost fertilizer application can improve lettuce tolerance to high temperatures. To determine the effectiveness of compost in improving yield quality under high temperature conditions.